The moment and the future: Kierkegaard's Oieblikket and Soloveitchik's view of repentance - Herskowitz, D (Cambridge University Press, 2016)
This article addresses the philosophical sources of Soloveitchik's unique account of time and repentance as presented particularly in the second part of Halakhic Man. In the past, thinkers such as Max Scheler, Hermann Cohen, and Henri Bergson have been suggested as sources of influence on Soloveitchik on this account. While the influence of these thinkers is undeniable, a fuller appreciation of the philosophical layers at play is still required. This article aims to show that the event of repentance in Soloveitchik's description is formulated in accordance with Kierkegaard's notion of Øieblikket (the moment), and to discuss the place of Heidegger in Soloveitchik's interpretation of repentance.